2022
DOI: 10.1021/acsnano.1c09681
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Inspired Mucin Coated Escherichia coli Nissle 1917 Enhances Biotherapy by Regulating the Pathological Microenvironment to Improve Intestinal Colonization

Abstract: The delivery of probiotics to the microbiota is a promising method to prevent and treat diseases. However, oral probiotics will suffer from gastrointestinal insults, especially the pathological microenvironment of inflammatory diseases such as reactive oxygen species (ROS) and the exhausted mucus layer, which can limit their survival and colonization in the intestinal tract. Inspired by the fact that probiotics colonized and grew in the mucus layer under physiological conditions, we developed a strategy for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…The high expression levels of Nrf2 and HO-1 can inhibit LPS-activated ROS production, thus decreasing the levels of pro-inflammatory cytokines in RAW 264.7 murine macrophages. These results are consistent with previous reports that probiotics participate in the modulation of inflammation-related diseases by regulating oxidative stress [ 20 , 21 ]. Compare to previous studies, the probiotics screened in the present study exhibited both strong anti-inflammatory and antioxidative properties [ 61 , 62 , 63 , 64 ], which were largely attributed to their secondary metabolites.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The high expression levels of Nrf2 and HO-1 can inhibit LPS-activated ROS production, thus decreasing the levels of pro-inflammatory cytokines in RAW 264.7 murine macrophages. These results are consistent with previous reports that probiotics participate in the modulation of inflammation-related diseases by regulating oxidative stress [ 20 , 21 ]. Compare to previous studies, the probiotics screened in the present study exhibited both strong anti-inflammatory and antioxidative properties [ 61 , 62 , 63 , 64 ], which were largely attributed to their secondary metabolites.…”
Section: Discussionsupporting
confidence: 94%
“…Oxidative stress is an excessive production of ROS, which can provoke the onset and progression of various diseases, including diabetes [ 16 ], cancer [ 17 ] and cardiovascular diseases [ 18 ], etc. Accumulating studies have suggested that intestinal flora metabolites may participate in the modulation of inflammation-related diseases through regulating oxidative stress [ 19 , 20 , 21 ]. Despite the evident potential, knowledge is scarce about the antioxidant effects of probiotics, as an alternative for various disease protection against oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests the interplay between the gut microbiome and IBD. Recently, some success in treatment of IBD has been achieved with strategies for modulating the gut microbiome. , To investigate the effect of oral administration of FALNP and FAL@CSA on gut microbiota composition in DSS-colitis mice, we performed 16S rRNA gene sequencing of fecal metabolites. Principal component analysis plots indicated distinct microbiota phylogenetic profiles among the normal, DSS-colitis, FALNP, and FAL@CSA treatment groups (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“… [ 56 ] Mucins and TA Microencapsulation The DSS induces the enteritis in the mice Mucins enhanced the colonization effect of ECN, and TA removed the superoxide radicals produced by inflammation. [ 57 ] PELA surface grafted functional groups (mannose group) or aminofibers Electrospinning / Synthetic fibers were used for the immobilization of ECN to improve the targeted colonization and survival of ECN. [ 58 ] Polydopamine microtubules of the glycan-loaded urokinase Electrospinning Mice with hindlimb vein thrombosis ECN as a driving device improved the bioavailability of urokinase for thrombosis.…”
Section: Surface Modified Ecnmentioning
confidence: 99%